Gambir Extract As A Corrosion Inhibitor For Mild Steel In Acidic Solution - Nofrizal Nofrizal (Scientific Contributions Oil and Gas, 2012)
The inhibition infl uence of Gambir extract in 1M Hidrocloric Medium on corrosion of mild steel in acidic solution was studied by weight loss measurements, potentiodynamic polarization, electrochemical impedance spectroscopy (EIS) and scanning electron microscope (SEM method. It is believed that the phenolic compounds that contained in the Gambir extract in 1 M Hidrocloric medium to be responsible for the inhibition. The corrosion studies shows that Gambir extract gives an anodic type of inhibition and best at the concentration of 150 ppm. The inhibition effi ciency for weight loss measurement, potentiodynamic polarization measurement, and electrochemical impedance spectroscopy were 76.52, 88.28 and 66.27% respectively. SEM analysis shows that the morphology of inhibited mild steel was improved compared with uninhibited mild steel.